Core inflation: a review of some conceptual issues - Mark A. Wynne (European Central Bank (ECB), 1999)
This paper reviews various approaches to the measurement of core inflation that have been proposed in recent years. The objective is to determine whether the ECB should pay special attention to one or other of these measures in assessing inflation developments in the euro area. I put particular emphasis on the conceptual and practical problems that arise in the measurement of core inflation, and propose some criteria that could be used by the ECB to choose a core inflation measure.
Keywords: C8; E0; E31; 330; core inflation